2021
DOI: 10.1155/2021/1661617
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental Disorder Traits in Taijin-Kyofu-sho and Social Anxiety Disorder: A Cross-Sectional Study among University Students

Abstract: Taijin-Kyofu-sho is an East Asian culture-bound anxiety disorder with similarities to social anxiety disorder. However, few studies have examined these two disorders from the perspective of neurodevelopmental disorders. This study is aimed at examining the association of Taijin-Kyofu-sho and social anxiety disorder with the attention-deficit/hyperactivity disorder (ADHD) trait and autism spectrum disorder (ASD) trait. The Liebowitz Social Anxiety, Taijin-Kyofu-sho, and Adult Attention-Deficit/Hyperactivity Dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“… Kajitani et al (2019) found a moderate positive correlation between the culture-specific taijin kyofusho and subdiagnostic ADHD, and a weak positive correlation between subdiagnostic social anxiety and ADHD, in university students. In another study, the prevalence of subdiagnostic ADHD was 45.3% in university students with subdiagnostic social anxiety, compared to 32.7% for taijin kyofusho, and 18.8% for no subdiagnostic social anxiety ( Kajitani et al, 2021 ). Studies that investigated diagnostic ADHD in adults with diagnostic SAD reported prevalence rates of 1.1% ( Peyre et al, 2022 ), 3% ( Safren et al, 2001 ), 7.8% ( Mörtberg et al, 2012 ), 38.5% ( Van Ameringen et al, 2011 ), 40.1% ( Umutlu et al, 2022 ), 58.2% ( Yoldas et al, 2019 ), 62% ( Koyuncu et al, 2019 ), and 72.3% ( Koyuncu et al, 2015 ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“… Kajitani et al (2019) found a moderate positive correlation between the culture-specific taijin kyofusho and subdiagnostic ADHD, and a weak positive correlation between subdiagnostic social anxiety and ADHD, in university students. In another study, the prevalence of subdiagnostic ADHD was 45.3% in university students with subdiagnostic social anxiety, compared to 32.7% for taijin kyofusho, and 18.8% for no subdiagnostic social anxiety ( Kajitani et al, 2021 ). Studies that investigated diagnostic ADHD in adults with diagnostic SAD reported prevalence rates of 1.1% ( Peyre et al, 2022 ), 3% ( Safren et al, 2001 ), 7.8% ( Mörtberg et al, 2012 ), 38.5% ( Van Ameringen et al, 2011 ), 40.1% ( Umutlu et al, 2022 ), 58.2% ( Yoldas et al, 2019 ), 62% ( Koyuncu et al, 2019 ), and 72.3% ( Koyuncu et al, 2015 ).…”
Section: Resultsmentioning
confidence: 97%
“…This can be problematic as both the prevalence of SAD and how SAD is manifested are associated with cultural factors (e.g., perceived social norms in a given cultural group; Hofmann et al, 2010 ). Additionally, three of the studies included culture-specific diagnoses of social anxiety, namely hikikomori ( Umeda et al, 2021 ) and Tajin-Kyofu-sho ( Kajitani et al, 2019 ; Kajitani et al, 2021 ). More research studies on cultural differences concerning SAD in general, and specifically comorbid SAD and ADHD, is therefore certainly warranted.…”
Section: Discussionmentioning
confidence: 99%